Tool And Die Design for the Prototype Fabrication of Automobile Pleated Air Filter - Maharjan, Sanjeev; Sharma, Amit; Kafle, Dinesh; Pathak, Sunil (KEC Journal of Science and Engineering, 2026)
Air filter is one of the important components of internal combustion engine driving system. In this study tool, die and fixtures that can be designed and assembled for the fabrication of air filter is presented. Dies were further heat treated for better hardness property so that it can press sheet metal. Then sheet metal was sandwiched in between these two dies and pressed together using flywheel press to fabricate pleat base. Effect of dry pressing, clearance, lubrication and removal of shearing angle for achieving quality finishing were thoroughly presented. Dry pressing result provided distorted pleat shape as shearing and wrinkles were obtained in the bending portion of pleat base. Due to this reason dies were redesigned and lubrication was introduced during pressing. Similarly, clearance and shearing angle were modified to achieve pleat base. After that perforated support and pleated air filter were fabricated and assembled together to fabricate an air filter.